Australia : Basel II Implementation Assessment. (IMF Staff Country Reports; Country Report ;, 2010)
The key findings of Australia's BASEL II implementation assessment are presented. The Australian Prudential Regulation Authority (APRA) allocated sufficient resources, including highly skilled staff, prior to the Basel II start date, and the outcome has been a robust and high-quality implementation that has built upon and substantially strengthened the risk-management capabilities of major banks. The quality of leadership and commitment by all involved has been instrumental in the success of this major implementation effort. APRA's analysis of the adequacy of capital for systemically relevant banks is sound.